The Mental State of a Person that Determines Labor Safety and Methods for Its Improvement - Shamsidinovna, Kamalova Makhfiza; Mamarasulovich, Achilov Anvar (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses mental conditions that affect the ability to work and the safety of a person's work.